Analisis Kebutuhan Pengguna Untuk Perancangan Aplikasi Database Laporan Keuangan Dengan Menggunakan Microsoft Access untuk UMKM - Oliyan, Fitra; Heriyanto, Randy; Septriani, Yossi; Tania, Kesha (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
Based on the observations conducted in the field, the financial recording in the company under study is still performed using a manual method, specifically through handwritten entries in a cash book. This recording process is limited to cash flow management, which includes tracking incoming and outgoing funds. To evaluate the availability of goods for purchase or sale, the business owner conducts physical checks at the storage location. Consequently, each transaction requires additional time for verification. In some cases, the owner is unaware that the requested inventory has run out during a sales transaction. This situation poses a significant obstacle for the owner in managing business operations. In response to the findings and issues faced, a simple accounting recording method that can directly generate financial reports using Microsoft Access is necessary. This research adopts a qualitative approach to gain a comprehensive understanding of user needs. The methods employed include interviews with the owner and analysis of the collected data and information. The study is conducted on a small and medium-sized enterprise (SME) in Padang that still utilizes a simple financial recording system. The outcome of this research is the creation of a database application for preparing financial reports designed according to user analysis needs